Organic Vegetable Enterprise Development In Bonto Bunga Village, Moncongloe Sub-District, Maros Regency - Andi Kasirang T. Baso; Suardi Bakri; Awaluddin Yunus; Nur Azizah; Dian Asri Unga Mega; Kartika Ekasari Z; Nur Rahmah; Anggi Kemalasari (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2026)
Jaring Tani is a startup engaged in the distribution of vegetables directly from local farmers to consumers. Along with the advancement of information technology, Jaring Tani has developed an online trading system based on social media platforms such as Instagram and WhatsApp. The impact of using these digital platforms has resulted in a significant increase in demand for organic vegetables, especially lettuce and pak choy, exceeding the existing production capacity. In response, Jaring Tani contributes to the development of modern agriculture by establishing a hydroponic garden named Madam Organic Garden. This study aims to: (1) analyze the utilization of digital platforms as promotional tools, (2) identify the influence of social media use on sales growth, and (3) design an effective agro-system development strategy using the APPAS method. The approach used in this research is qualitative descriptive. The findings reveal that the marketing strategy implemented by Madam Organic Garden is still limited to distributing flyers through WhatsApp and Instagram. The implementation of digital marketing has proven capable of expanding market reach and increasing consumer awareness. Through applying the APPAS method, the optimal development strategy is obtained in the stage of designing transformative actions, following the process of case study and problematization, aimed at addressing the main issue of production capacity that has not yet met market demand.